Adopting the “Explain EDU” application approach in teaching mathematics and statistics / Nur Hidayah Md Noh ... [et al.] - Md Noh, Nur Hidayah; Yusoff, Sarah; Hassanuddin, Nor Aini; Mohamad Sukri, Nursyazni (2021)
Interactive whiteboards (IWB) is known as one of the most revolutionary instructional technologies for various educational levels. One of the popular applications among educators that can be used as an extremely versatile interactive whiteboard is 'Explain EDU' (EEDU) application. EEDU works as a platform for borderless learning, sharing and collaborating using an IWB. It is an iPad app that is used to create dynamic lessons, presentations and other content that can be easily shared with others. Students who participated in this study are those from Faculty of Computer and Mathematical Sciences who enrolled in a mathematics or statistics course at Universiti Teknologi MARA (UiTM) Terengganu during the March – July 2019 semester. This study aims to gain insight on students' opinions and perspectives in learning Mathematics and Statistics subjects when being taught by using the EEDU application. The result suggests that the use of Explain EDU application in class for teaching does enhance students attitude towards learning mathematics or statistics course.